Irrigation Water Quality and Crop Yield Relationship Established for Kaithal Irrigation Circle of Bhakra System - Chandra, Ravish; Tyagi, N K; Sakthivadivel, R (Journal of Agricultural Engineering, 2009)
Salinity is one of the major problems of irrigated agriculture all over the world. More than 60 % of the land is underlain by saline ground water in North West India. The knowledge of relationship between irrigation water quality (EC) and crop yield is essential for management of surface water and ground water for higher profitability. In the present study, an attempt was made to evaluate the irrigation water quality and wheat yield relationship for Kaithal irrigation circle of Bhakra canal command. Information on EC, agronomic practices, crop yield etc. were collected from 108 farms comprising 36 farms each from head, middle and tail watercourses of Batta minor. The presence of different quality of ground water creates large variation in crop yield. To establish a relationship between irrigation water quality and crop yield of wheat, several types of functions were tried and form of relationship generating highest correlation coefficient was selected as most appropriate relationship. The polynomial equation of fifth order was most suitable for irrigation water quality and crop yield relationship. This relationship can be used for estimating wheat yield with different quality of water. The groundwater of the tail reaches being saline in nature was about 25% less productive as compared to head reaches. The wheat yield in the tail was less by 10% as compared to head reaches due to unavailability of canal water and poor quality of ground water. Groundwater transfer from head to tail reaches and cultivation of low water requiring salt tolerant crop would be helpful in reducing the productivity gap and increasing the profitability of the farmers.